Pelatihan Penggunaan Teknologi Informasi Untuk Guru Sekolah Menengah Pertama Di Wilayah Lampung Utara - Roni Sapri; Yuni Kartika; Ari Wibowo; Sulastri; Dimas Prasetyo; Feri Irawan; Rika Novitasari (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2025)
Digital transformation in education demands that teachers possess adequate information technology competencies. However, middle school teachers in Lampung Utara still face challenges in integrating technology into their teaching. The goal of this activity is to improve teachers' competencies in using digital platforms, multimedia learning tools, and technology-based assessments. The implementation methods include workshops, mentoring, and continuous evaluation over three months, involving 45 teachers from 15 schools. The results show a significant increase in teachers' digital literacy by 78%, an 85% rise in the use of interactive learning media, and an 82% improvement in managing virtual classrooms. In conclusion, systematic training and ongoing mentoring are effective in enhancing teachers' digital literacy and encouraging innovation in learning in the digital era.